2017
DOI: 10.3390/ph10020039
|View full text |Cite
|
Sign up to set email alerts
|

Role of TRPM7 in Cancer: Potential as Molecular Biomarker and Therapeutic Target

Abstract: The transient receptor potential melastatin-subfamily member 7 (TRPM7) is a ubiquitously expressed ion channel with intrinsic kinase activity. Molecular and electrophysiological analyses of the structure and activity of TRPM7 have revealed functional coupling of its channel and kinase activity. Studies have indicated the important roles of TRPM7 channel-kinase in fundamental cellular processes, physiological responses, and embryonic development. Accumulating evidence has shown that TRPM7 is aberrantly expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 82 publications
2
67
0
Order By: Relevance
“…Nevertheless, taking into account the MI and the tumour location, the CFA 30 amplification was not any more significant, probably because of its strong association with the MI. Indeed, genes lying on this recurrent amplified region probably bring an advantage for the proliferation and progression of the tumour, such as TRPM7 involved in the MAPK pathway . Focal amplifications along CFA 10 were often found in two distinct regions covering the targeted genes MDM2 and the cycline‐dependent‐kinase CDK4 , and this association was demonstrated in a previous study .…”
Section: Discussionsupporting
confidence: 51%
“…Nevertheless, taking into account the MI and the tumour location, the CFA 30 amplification was not any more significant, probably because of its strong association with the MI. Indeed, genes lying on this recurrent amplified region probably bring an advantage for the proliferation and progression of the tumour, such as TRPM7 involved in the MAPK pathway . Focal amplifications along CFA 10 were often found in two distinct regions covering the targeted genes MDM2 and the cycline‐dependent‐kinase CDK4 , and this association was demonstrated in a previous study .…”
Section: Discussionsupporting
confidence: 51%
“…In as much as the mechanism of TRPM7 regulation of the cell cycle is still unclear and may involve some cell cycle checkpoint signaling [40], we found that the channel function of TRPM7 promotes the activity of cells in the G1 and S phases. This is in agreement with a previous finding that the Ca 2+ and Mg 2+ influx mediated by TRPM7 channels improves the activities of cells in the S phase [8,41].…”
Section: Discussionsupporting
confidence: 94%
“…There is a tendency for worse outcomes when the TRPM7 gene is highly expressed ( Figure S3). TRPM7 is found to be more highly expressed in some types of human cancer tissue compared to adjacent non-tumor tissue [24] and is thought to be associated with cancer development [8]. The effect of TRPM7 is complex because it affects cells both by regulating the flux of divalent cations into the cell and by regulating intracellular processes via the enzymatic activity of the kinase domain in its C-terminal region [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient receptor potential melastatin 7 (TRPM7) is a ubiquitously expressed ion channel with intrinsic kinase activity (5). Review studies have indicated the important roles of TRPM7 channel kinase in fundamental cellular processes, physiologic responses, and embryonic development (5,6). Accumulating evidence has shown that TRPM7 is aberrantly expressed and/ or activated in human diseases including cancer, and plays a variety of functional roles in cancer cells including survival, cell-cycle progression, proliferation, growth, migration, invasion, and epithelial-mesenchymal transition (5,6).…”
Section: Introductionmentioning
confidence: 99%